2007
DOI: 10.1158/1055-9965.epi-07-0061
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Activity with Reproductive Hormones: The Penn Ovarian Aging Study

Abstract: Background: Physical activity is associated with reduced risk for breast cancer, perhaps through reductions in circulating reproductive hormones (estrogens and androgens). There may also be a role for physical activity in regulating menopausal symptoms. Few studies have examined associations of physical activity on hormone levels. None have examined the potential effect of the menopausal transition on the associations between physical activity and reproductive hormone levels. Materials and Methods: Data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
2
18
1
Order By: Relevance
“…Most of the earlier published studies also reported an inverse association with estrogens (6,8,(11)(12)(13) and a positive association with SHBG (8,11). No association between physical activity and these hormones were found by the studies of Bjornerem et al (27) and Madigan et al (9).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Most of the earlier published studies also reported an inverse association with estrogens (6,8,(11)(12)(13) and a positive association with SHBG (8,11). No association between physical activity and these hormones were found by the studies of Bjornerem et al (27) and Madigan et al (9).…”
Section: Discussionmentioning
confidence: 92%
“…Few studies have investigated the relationship between physical activity and androgens (testosterone and androstenedione) in postmenopausal women (8)(9)(10)13), and all have reported an inverse association. In our study, however, we did not observe any association between usual physical activity and androstenedione/ testosterone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of physical activity on sex hormones may vary according to hormone receptor status (Sieri et al 2009), across the menopausal transition (Schmitz et al 2007), and also with body fat (McTiernan et al 2004a;McTiernan et al 2004b). Three RCTs have examined the effect of exercise on sex hormone levels and weight change in postmenopausal women.…”
Section: Sex Hormonesmentioning
confidence: 99%